PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKTAKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI PENGUKURAN PANJANG DAN BERAT DI KELAS III SD - Winda Oktaviana; Rohman, Fatkhur; Sari, Ika Kartika; Nurhanurawati; Oriyanti, Berta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the level of validity, practicality, and effectiveness of the developed product, which is the PBL-based LKPD, to enhance critical thinking skills in the topics of Length and Weight measurement in 3rd-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The validation results of the PBL-based LKPD show high scores in the content aspect (0.9305), language aspect (0.9472), and graphic design aspect (0.9652), indicating that this product is aligned with learning objectives, easy to understand, and has a supporting visual design. The practicality test shows ease of use by teachers (92%) and students (90%) and the ability to motivate students to actively participate. The N-Gain test demonstrates a significant improvement in students' critical thinking skills with a score of 0.743. Overall, this LKPD is valid, practical, and effective in enhancing critical thinking skills, making it an ideal recommendation for mathematics learning in elementary schools.